Impact social rehabilitation program on quality of life of inmates with illicit drug use - Megah Andriany; Refonda Rias Anggiri (Jurnal Keperawatan Padjadjaran, 2025)
Background: Inmates with illicit drug use have experienced various problems that affect their Quality of Life (QoL). The social rehabilitation program is expected to improve their QoL. Studies investigating the impact of social rehabilitation programs on QoL of inmates with drug abuse are limited. Purpose: This study aims to describe the differences in the QoL of inmates with illicit drug use at the 0, 3rd, and 6th months of the program and to know the program's effectiveness in three Indonesian prisons. Methods: This study used a secondary data analysis of comparison study with pre-post program intervention for inmates with illicit drugs in Indonesian Prisons by analyzing inmates' QoL. The instrument used the World Health Organization Quality of Life-BREF (WHOQOL-BREF). This study consists of documents from 400 male and 92 female inmates with illicit drug use who fully participate in social rehabilitation programs in three prisons. Data were analyzed by measuring the frequency and mean of QoL in the 0, 3rd, and 6th months using the One-Way Anova and the Kruskal Wallis to evaluate the program's effect on the QoL. Results: The average QoL in physical, psychological, social relationship, and environment domains increased from the 0, to 3rd, and 6th months of the program. The rehabilitation program was effective in improving QoL (p<0.001) in Prisons A and C, but it was found no significant effect on QoL in Prison B (p=0.069). Conclusions:  The rehabilitation program was potentially effective in improving the QoL of inmates with illicit drug use. It is important for related parties to further evaluate the supporting and inhibiting factors that affect the QoL in the social rehabilitation program and overcome these inhibiting factors.